1996
DOI: 10.1108/08876049610148602
|View full text |Cite
|
Sign up to set email alerts
|

SERVQUAL revisited: a critical review of service quality

Abstract: As competition becomes more intense and environmental factors become more hostile, the concern for service quality grows. If service quality is to become the cornerstone of marketing strategy, the marketer must have the means to measure it. The most popular measure of service quality is SERVQUAL, an instrument developed by Parasuraman et al. (1985; 1988). Not only has research on this instrument been widely cited in the marketing literature, but also its use in industry has been quite widespread (Brown et al.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
446
0
42

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 719 publications
(496 citation statements)
references
References 21 publications
8
446
0
42
Order By: Relevance
“…Accordingly, the use of online tax system as a new information technology is to achieve an effective tax admiration system. Chang et al [21] found that the effective use of online tax system are related to the tax service quality provided by the tax authority which also have effect on the cost reduction from the taxpayers and tax authority.…”
Section: Literaturementioning
confidence: 99%
“…Accordingly, the use of online tax system as a new information technology is to achieve an effective tax admiration system. Chang et al [21] found that the effective use of online tax system are related to the tax service quality provided by the tax authority which also have effect on the cost reduction from the taxpayers and tax authority.…”
Section: Literaturementioning
confidence: 99%
“…Asubonteng et al, 1996;Buttle, 1996). The application of the SERVQUAL scale in retail context resulted in the conclusion that the instrument does not adequately tap into service quality construct in retailing and that it should be refined taking into account specificities of service provision in retailing (Dabholkar et al, 1996).…”
Section: Retail Service Qualitymentioning
confidence: 99%
“…To measure satisfaction, however, users simply evaluate a single service encounter. The exact relationship between the two measurements has not yet been determined (Asubonteng, McCleary, & Swan, 1996).…”
Section: Service Quality Measurementmentioning
confidence: 99%